2007
DOI: 10.1073/pnas.0702622104
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent heme kinetics with nonexponential binding and barrier relaxation in the absence of protein conformational substates

Abstract: We present temperature-dependent kinetic measurements of ultrafast diatomic ligand binding to the ''bare'' protoheme (L 1-FePPIX-L 2, where L1 ‫؍‬ H2O or 2-methyl imidazole and L2 ‫؍‬ CO or NO). We found that the binding of CO is temperature-dependent and nonexponential over many decades in time, whereas the binding of NO is exponential and temperature-independent. The nonexponential nature of CO binding to protoheme, as well as its relaxation above the solvent glass transition, mimics the kinetics of CO bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
195
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(205 citation statements)
references
References 48 publications
9
195
1
Order By: Relevance
“…28,63,64 For example, heme ruffling has been suggested 65 to be a distortion that is involved in stabilizing the net positive charge of the ferric heme in nitrophorin (NP4). The general picture that needs to be explored is whether or not the protein matrix interacts with the normally planar heme and causes it to adopt conformations that enhance or retard specific reactions.…”
Section: Functional Roles and Dephasingmentioning
confidence: 99%
See 4 more Smart Citations
“…28,63,64 For example, heme ruffling has been suggested 65 to be a distortion that is involved in stabilizing the net positive charge of the ferric heme in nitrophorin (NP4). The general picture that needs to be explored is whether or not the protein matrix interacts with the normally planar heme and causes it to adopt conformations that enhance or retard specific reactions.…”
Section: Functional Roles and Dephasingmentioning
confidence: 99%
“…67 Recent kinetic studies have revealed a significant amount of inhomogeneity that is inherent to the heme group in solution, but it appears that the inhomogeneous distributions are some-what larger in the protein. 28 Further experimental testing of these ideas will require temperature-dependent measurements of the coherence spectra of heme model compounds.…”
Section: Thermal Effectsmentioning
confidence: 99%
See 3 more Smart Citations